A real-world cost-effectiveness analysis of nebulized budesonide and intravenous methylprednisolone in acute exacerbation of chronic obstructive pulmonary disease - Gu, Yong-Li; Sun, Zeng-Xian; Sun, Ying; Wen, Yan; Guan, Xin; Jiang, Dao-Li; Cheng, Cong; Gu, Huan (Frontiers in Pharmacology, 2022)
Objective: To assess the cost-effectiveness of nebulized budesonide and intravenous methylprednisolone in the treatment of acute exacerbation of chronic obstructive pulmonary disease (AECOPD) in a real-world setting. Materials and methods: Data from 194 patients with AECOPD were collected from the information system of a tertiary hospital in China. Patients were categorized into two groups: those treated with nebulized budesonide (n = 95) and those treated with intravenous methylprednisolone (n = 99). Clinical efficacy and the rate of no readmission within 1 year after discharge were used as effect indicators, and a cost-effectiveness analysis was conducted from the perspective of the Chinese healthcare system. Logistic regression, generalized linear regression, and bootstrap methods were used for sensitivity analyses. Results: There was no statistical difference between the budesonide and methylprednisolone groups in clinical efficacy rates (94.7% vs. 93.9%). The cost-minimization analysis shows that budesonide is not cost-effective owing to higher total cost. In terms of readmission rates, budesonide was again not cost-effective, with an incremental cost-effectiveness ratio (ICER) of 22,187.23 CNY, which is higher than the willingness to pay (WTP) of 20206.20 CNY, the mean per admission expenditure in China. The sensitivity analyses confirm that these results are robust. Conclusions: Compared with intravenous methylprednisolone, nebulized budesonide is not a cost-effective strategy for AECOPD patients in China.